Impact of Physical Exercise on College Students' Loneliness: The Mediating Role of Social Support - Ma, Chaoyi; Johnston, Dan; Kim, Kyungyeol; Zhang, Yi (Advances in Social Sciences Research Journal, 2024)
This study examines the impact of physical exercise on loneliness among college students, as well as the role of social support as a mediating variable. An online questionnaire measuring loneliness, physical exercise level, and social support was administered to a sample of 1,175 college students in China. Structural equation modeling analysis shows the significant negative effect of physical exercise on loneliness. Social support is found to be negatively associated with loneliness. Social support plays a partial mediating role. The preset research introduces social support as an intermediary variable, which highlights its significance in enhancing physical exercise and reducing a sense of loneliness for college-age individuals